Exact special solutions to the nonlinear dispersive K (2,2,1) and K(3,3,1) equations by He's variational iteration method - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2008)
We implemented a variational method for approximating the solution to the nonlinear dispersive K(m, p, l)-type equations. By using this scheme, the explicit exact solution is calculated in the form of a quickly convergent series with easily computable components. To illustrate the application of this method, numerical results are derived by using the calculated components of the variational series. The obtained results are found to be in good agreement with the exact solution. (C) 2007 Elsevier Ltd. All rights reserved.
Keywords: nonlinear dispersive K (m, p, l) equations; variational iteration method; Lagrange multiplier